2014
DOI: 10.1074/jbc.m114.600288
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like Nanofibrils of Small Molecules (PriSM) Selectively Inhibit Cancer Cells by Impeding Cytoskeleton Dynamics

Abstract: Background: Small molecules form prion-like nanofibrils termed as PriSM. Results: PriSM accumulate selectively in cancer cells and impede cytoskeleton dynamics. Conclusion: PriSM is selectively toxic to cancer cells. Significance: We hope this work will inspire the exploration of PriSM, formed by hydrophobic peptides, as a new paradigm of polypharmacological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 48 publications
(47 reference statements)
2
58
0
Order By: Relevance
“…We have been exploring enzyme-instructed molecular self-assembly [5] inside cells, [6] and our recent study shows that intracellular molecular nanofibers promiscuously interact with cytoskeleton proteins [7] yet selectively inhibit cancer cells. [8] Recently, Maruyama et al, [9] Pires and Ulijn, [10] Yang et al, [11] and Wells [12] also reported inhibition of cancer cells by nanofibers formed by the self-assembly of small molecules.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have been exploring enzyme-instructed molecular self-assembly [5] inside cells, [6] and our recent study shows that intracellular molecular nanofibers promiscuously interact with cytoskeleton proteins [7] yet selectively inhibit cancer cells. [8] Recently, Maruyama et al, [9] Pires and Ulijn, [10] Yang et al, [11] and Wells [12] also reported inhibition of cancer cells by nanofibers formed by the self-assembly of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The genome analysis according to The Cancer Genome Atlas (TCGA) indicates the amplification of CES in certain tumors (e.g., breast and ovarian cancer) ( Figure S23), which not only supports the observation in this work, but also provides useful guidance for treating other cancers based on this approach. This work, together with other emerging evidence, [6][7][8][9][10]12] indicates that enzyme-instructed self-assembly promises a new way for developing combination therapy for cancer treatment. Other than cisplatin, carboplatin has been used as the preferred platinum-based drug [20] and we will use carboplatin for our future work.…”
mentioning
confidence: 99%
See 3 more Smart Citations